Higher diagnostic value of metagenomic next-generation sequencing in acute infection than chronic infection: a multicenter retrospective study - Yao, Anjie; Wang, Jiale; Xu, Qintao; Shah, Binay Kumar; Sun, Kai; Hu, Feng; Wang, Changhui; Xie, Shuanshuan (Frontiers in Microbiology, 2024)
Background The aim of this study is to compare the diagnostic value of metagenomic next-generation sequencing (mNGS) vs. conventional culture methods (CM) in chronic infection and acute infection. Methods We retrospectively analyzed the bronchoalveolar lavage fluid (BALF) of 88 patients with acute infection and 105 patients with chronic infection admitted to three hospitals from 2017 to 2022. Results The results showed that the sensitivity and specificity of mNGS were higher than those of CM. The number of patients who changed the antibiotic treatment in the mNGS positive group was larger than that of patients in the mNGS negative group in both the acute infection group (60.5 vs. 28.0%, P = 0.0022) and chronic infection group (46.2 vs. 22.6%, P = 0.01112). High levels of temperature (OR: 2.02, 95% CI: 1.18–3.70, P: 0.015), C-reactive protein (CRP) (OR: 15, 95% CI: 2.74–280.69, P: 0.011), neutrophil count (OR: 3.09, 95% CI: 1.19–8.43, P: 0.023), and low levels of lymphocyte count (OR: 3.43, 95% CI:1.26–10.21, P: 0.020) may lead to positive mNGS results in the acute infection group while no significant factor was identified to predict positive results in the chronic infection group. Conclusion mNGS could provide useful guidance on antibiotic strategies in infectious diseases and may be more valuable for the diagnosis and treatment of acute infection vs. chronic infection.